Public private partnership in the development strategy of tambi agro-tourism in the community based tourism - Ridwanca, Ardian; Fachrizal Nurhamzah (Institute of Computer Science (IOCS), 2024)
Tourism has grown into a major industry with significant economic influence in many countries. In Indonesia, agrotourism has emerged as a promising form of tourism, especially with its potential in supporting local economic development and sustainable use of natural resources. This study focuses on Tambi Agrotourism in Wonosobo Regency, Central Java, as an example of implementing Community Based Tourism (CBT) with the Public Private Partnership model. Active stakeholder participation in the process of developing and implementing effective communication is the key to success in promoting and managing Tambi Agrotourism. A well-planned communication strategy is very important in facing challenges and exploiting opportunities that exist in agrotourism development. The research method used is a qualitative case study, with a SWOT analysis approach to identify relevant strengths, weaknesses, opportunities and threats in the context of Tambi Agrotourism development. The results of this research illustrate the importance of collaboration between government, private sector and local communities in developing sustainable and highly competitive tourism destinations. This research also underlines the need for effective communication as a crucial element in maintaining harmony and promoting Tambi Agrotourism to visitors clearly and accurately.